Fijación de fosforo en sedimientos de fondo de los Ríos Paraná, Paraguay y Bermejo - Pedrozo, Fernando L.; Bonetto, Carlos A.; Ramos, Abel; Minzoni, Ferrucio (Ecosur, 2023)
Phosphorus sorption'from Solutions containing 0-5 mgP/l was studied in bottom sediments from Paraná, Paraguay and Bermejo rivers. Sorptidh frtted a Langmuir isotherm with phosphate sorption capacities of 96, 87 and 52 MgP/g (dry weight) sediment. Hieltjesand Lijklema (1980) phosphorus fractionation showed that the iron bound phosphate is the mainfraction in the Paraná and Paraguay sediments while the calcium bound phosphorus is the main fraction in the Bermejo sediments. Caleiuhi content was high (32 mg/g) in the Bermejo sediments and low (5.5 and 5;3 mg/g) in the Paraná and Paraguay sediments, respectively, The organic matter composition is also dlfferent in the three rivers being the Paraná and the l^íraguay ríchér in huihic ^ibstánces. Low phosphorus content and sorption capacity in the three sediments are thought to be related with a granulometry dominated by the coarse fractions. Clay size partióles only accounted for 13-23 % of the total sediment weight.